Removal of nitrate onto spent mushroom compost in a fixed-bed column - Mohammedd Abdulraheem Mahfoudh Bamasood (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
In this study, the Spent Mushroom Substrate (SMS) was prepared by two different methods, which the SMS were washed by water and other method without washing. Then, for SMS pretreatment, the SMS was treated by acid and alkali. The adsorption capacity of the treated and untreated SMS was studied by conducting the batch experiment to evaluate the best method of preparation and pretreatment. Continuous experiment was conducted in a fixed-bed column using the best sample estimated from batch experiment. The process parameters of continuous experiment were flow rate of nitrate solution in range of 10 - 30 ml/min, bed height in range of 4 - 16 cm and initial concentration of nitrate in range of 500 - 800 mg/L. The results were analyzed in terms of breakthrough curve and nitrate removal percentage. The result of batch experiment shown the SMS that prepared without washing by water and pretreated with potassium hydroxide was the best sample and performed the highest nitrate removal percentage among the other samples. The result for continuous experiment shows that the nitrate removal percentage increasing with the decrease of the flow rate, which the higher nitrate removal percentage was observed at flow rate of 10 ml/min. For the effect of bed height, the nitrate removal percentage was increased, with the increasing of the bed height with, the highest nitrate removal percentage was observed at bed height of 16 cm. The nitrate removal percentage increase as the initial concentration decrease from 800 to 500 mg/L in this study. Finally the best condition for nitrate removal in the fixed-bed column was 10 ml/min for flow rate, 16 cm for bed height and 500 mg/L for initial concentration.